STUDY REGARDING THE IMPORTANCE OF CHEERLEADING EXTRACURRICULAR ACTIVITIES IN THE PRIMARY SCHOOL - Tatiana Dobrescu (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The aim of this paper is to bring to the attention of teachers the effectiveness of certain new strategic models for education, by presenting one of the most dynamic branches of extracurricular activities - cheerleading. The research was conducted during the academic year 2014-2015, in School no. 1, Nicolae Bălcescu, Bacau county, a school that has limited material conditions and resources for conducting proper physical education lessons. The accessibility of the choreographies and pyramids that were performed ensures the participation of all pupils, no matter their somatic or motor abilities. Cheerleading offers modern, operational alternatives, influencing the motor behavior in primary pupils, creating an agreeable working environment, which confirms the hypothesis formulated in the beginning of the research.